Ewolucja systemu zasilania finansowego jednostek samorządu terytorialnego w Polsce - Peter-Bombik, Katarzyna (The Evolution of the System of the Financial Support of Local Government in Poland, 2007)
The Evolution of the System of the Financial Support of Local Government in Poland
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 498-508